Law enforcement officers’ perceptions of and responses to traumatic events: a survey of officers completing Crisis Intervention Team training - Fleischmann, Matthew H. (Policing and society, 2018)
Law enforcement officers work in ever-changing and sometimes stressful environments. However, to date, little research has been conducted on officers’ perceptions of, and responses to, stressful and traumatic events. We surveyed 575 officers in Crisis Intervention Team (CIT) training regarding such perceptions and responses. Results indicate that many officers have experienced traumatic events, and/or know a fellow officer who has experienced trauma on the job. Yet, these officers are reluctant to disclose their experiences to their agency. Moreover, results indicate that many officers are hesitant to seek help within their agency, suggesting barriers such as pervasive stigma. Results also indicate that agencies are providing some resources (e.g. training) to help their officers cope; yet the empirical evidence on this is scant. We expect that our findings will help contribute to the literature on CIT and interactions between officers and persons with mental illnesses, and inspire new, rigorous training and programme development.